2017
DOI: 10.14303/jmms.2016.143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of cord clamping on neonatal venous hematocrit and clinical outcome at term hospital based randomized control trial

Abstract: The study was conducted at the department of Obstetrics and Gynecology at Jawaharlal Nehru Medical College, Aligarh India from June 2008 to October 2010. 200 mothers were selected for the study and informed consent using a predesigned proforma. The subjects were divided into 4 groups of 50 each wherein the umbilical cord was clamped at 15 seconds, 30 seconds, 1 minute and 2 minutes respectively. The neonatal venous hematocrit and clinical outcome was assessed. The primary objective was to study the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…[36] Though enhancements in hemoglobin concentrations are more passing, newborns delivery ECC have decreased iron stores and are twice as likely to be iron deficient at three to six months of age in his study aboutΑ quality improvement initiative for delayed umbilical cord clamping in very-low-birth-weight infants at Department of Neonatology, Christiаna Care Health System USΑ. In agreement with Ishtiaq & Bano (2013) who found that the prevalence of neonatal anemia at six hrs was more when the cord was clamped early. In group (1), 8% neonates were set up anemic with no incidence of polycythemia.…”
Section: American Research Journal Of Nursingsupporting
confidence: 90%
See 1 more Smart Citation
“…[36] Though enhancements in hemoglobin concentrations are more passing, newborns delivery ECC have decreased iron stores and are twice as likely to be iron deficient at three to six months of age in his study aboutΑ quality improvement initiative for delayed umbilical cord clamping in very-low-birth-weight infants at Department of Neonatology, Christiаna Care Health System USΑ. In agreement with Ishtiaq & Bano (2013) who found that the prevalence of neonatal anemia at six hrs was more when the cord was clamped early. In group (1), 8% neonates were set up anemic with no incidence of polycythemia.…”
Section: American Research Journal Of Nursingsupporting
confidence: 90%
“…Which the study sample was divided into 4 groups of 50 each wherein the umbilical cord was clamped at 15 seconds, 30 seconds, 1 minute and 2 minutes respectively. [37] Polycythemiа or a hemаtocrit level of >65% at birth & after 24 hours among early & late group was lower in ECC but higher among the late cord clamping group compared to early cord clamping, this result supported by Ishtiaq & Bano (2013) who stated that,in group 4 polycythemia occurred in 6% of cases and no found anemic…”
Section: American Research Journal Of Nursingmentioning
confidence: 81%
“…Intervention to reduce anaemia during first six months of life 9 . Others realize that blood overload from delayed cord clamping can produce respiratory distress, polycythemia and jaundice 10,11 . while with early cord clamping maternal blood loss following birth can be reduced significantly 12 .…”
mentioning
confidence: 99%